1969
DOI: 10.1007/bf02531015
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of phospholipids in the triglyceride cycle: II. Turnover of plasma phospholipids in ethionine‐treated dogs

Abstract: The disappearance of native labeled plasma phospholipids (nPLP32) was abruptly halted in the plasma of normal mongrel dogs shortly after givingdl‐ethionine by intraperitoneal injection. In other dogs, chronic feeding of ethionine over a period of three days prior to these measurements prolonged the turnover time of plasma phospholipids. This impairment in the turnover of plasma PL brought about by ethionine administration occurs regardless of sex differences in lipid metabolism or other physiological differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1971
1971
1971
1971

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The vehicle for this transport is lipoprotein, the water soluble lipid complexes which have been studied extensively and presented in this symposium by Dr. Lopez (14). Results of previously published portions of the present study (15,16) indicated that liver lipid mobilization required de novo synthesis of liver lecithins.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…The vehicle for this transport is lipoprotein, the water soluble lipid complexes which have been studied extensively and presented in this symposium by Dr. Lopez (14). Results of previously published portions of the present study (15,16) indicated that liver lipid mobilization required de novo synthesis of liver lecithins.…”
Section: Introductionmentioning
confidence: 59%
“…Changes in the RSA during the course of fasting suggested increased mobilization of liver PL at times when liver TG cycling would be enhanced. In normal dogs (16), ethionine blocks LIPIDS, VOL. 6, NO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations